Conjoined twins (Siamese) in guinea pigs (Cavia porcellus): description of anatomopathological findings of a case of cephalothoracoonphalopagus - D. Zea-Gonzales; K. Taype-Rivera; F. Lozano (Arquivo Brasileiro de Medicina Veterinária e Zootecnia)
ABSTRACT The objective of the research was to describe the physical characteristics, through X-rays and necropsy in conjoined twins (Siamese twins) of female guinea pigs (Cavia porcellus). The study sample was located in Cusco, Peru. The methodology used was descriptive. The conjoined twins of cephalothoracoonphalopagus type in guinea pigs (Cavia porcellus) were stillborn from a female guinea pig (type 1). The stillborn was subjected to radiographic evaluation and a single skull and two distinct vertebral columns were observed. Anatomopathological examination revealed the head, thoracic cavity and umbilicus as the main attachment point. They were classified as cephalothoracoonphalopagus type. After necropsy they had one head, one face, two developed eyes, and one eye in the posterior part of the skull, two nostrils, four auricular pavilions, one oral cavity plus tongue, two pairs of thoracic extremities, two umbilici. The respiratory system consisted of two well-formed nostrils, one guinea pig had no lungs, two thoracic cavities, two hearts and two diaphragms, which separated the two thoracic cavities from the single abdominal cavity. In conclusion, it is remarkable that congenital malformations occur very rarely, this malformation is rare in domestic animals. Further research on the causes of this congenital anomaly is needed.